2014
DOI: 10.1152/ajpgi.00208.2013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the motor inhibitory role of colonic mucosa under chemical stimulation in mice

Abstract: Martín-Cano FE, Camello PJ, Pozo MJ. Characterization of the motor inhibitory role of colonic mucosa under chemical stimulation in mice. Am J Physiol Gastrointest Liver Physiol 306: G614 -G621, 2014. First published February 13, 2014 doi:10.1152/ajpgi.00208.2013The main roles of the colonic mucosa are the absorption of water and electrolytes and the barrier function that preserves the integrity of the colonic wall. The mediators and mechanisms to accomplish these functions are under continuous investigation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…An excellent work using haem oxygenase‐2‐KO (Sha et al , ) and CSE KO mice (Sha et al , ) demonstrated that the transwall gradient is probably due to CO and potentiated by H 2 S. Both NO and CO are possibly released by SMP neurons. CO and H 2 S produced by the mucosa itself might also contribute to inhibit motility in the circular layer (Martin‐Cano et al , ). The consequence of this organization is that SMCs near the SMP are considerably more hyperpolarized than the cells near the MP and have the ability to oscillate at a frequency paced by ICC‐SMP (Mane et al , ).…”
Section: Participation Of H2s In the Transwall Gradient Of Smooth Musmentioning
confidence: 99%
“…An excellent work using haem oxygenase‐2‐KO (Sha et al , ) and CSE KO mice (Sha et al , ) demonstrated that the transwall gradient is probably due to CO and potentiated by H 2 S. Both NO and CO are possibly released by SMP neurons. CO and H 2 S produced by the mucosa itself might also contribute to inhibit motility in the circular layer (Martin‐Cano et al , ). The consequence of this organization is that SMCs near the SMP are considerably more hyperpolarized than the cells near the MP and have the ability to oscillate at a frequency paced by ICC‐SMP (Mane et al , ).…”
Section: Participation Of H2s In the Transwall Gradient Of Smooth Musmentioning
confidence: 99%
“…This contractile response is indicative of a nervous reflex that is abolished by tetrodotoxin and reduced by atropine and tackykinin antagonists[26]. Activation of enteric nerves by EFS mimics the in vivo conditions in which neurotransmitters are released by motor neurons to the neuroeffector apparatus; the interaction between the interstitial cells of Cajal, neurons, glial cells and smooth muscle cells generates contraction[27,28]. …”
Section: Methodsmentioning
confidence: 99%